COVID 19 in Brazil : Impacts and Policy Responses - World Bank (World Bank, Washington, DC, 2020)
The COVID-19 (Coronavirus) pandemic is exposing Brazil to an unprecedented challenge. The pandemic is expected to plunge Brazil into another recession. Although the pain of recession can be felt across the economy, smaller firms are expected to be more affected because they tend to be more present in sectors with high face-to-face interactions, and where home-based work is less pervasive. State (and municipal) governments constitute a third group that is highly exposed to the crisis. Special attention will need to be devoted to the infrastructure sector, including energy, water, and transport, due to their strategic nature in the economy and potential contingent liabilities for the government. The financial sector was in a position of strength when the COVID-19 crisis started, and it will play a critical role during both the crisis and the recovery phase. Brazil has already put in place significant measures to address the economic crisis. Beyond the immediate containment of the crisis, Brazil will need to focus on laying the groundwork for a speedy and equitable recovery.